Clean 3,4-Dihydropyrimidones Synthesis via Biginelli Reaction over Supported Molybdenum: Structural and Textural Characteristic of αMoO3 - Ouzna Kheffache; Cristina Lopez-Olmos; Inmaculada Rodriguez-Ramos; Ouiza Cherifi (Bulletin of Chemical Reaction Engineering & Catalysis, 2020)
A one-pot three-component synthesis of dihydropyrimidinones (DHPMs) via Biginelli reaction was carried out at 100 °C using benzaldehyde, ethyl acetoacetate and urea as reactants, in the presence of ethanol and free solvent, in heterogeneous catalytic medium. The Mo (30 wt%) metal oxides (Al2O3, SiO2 or MgO) used catalysts were prepared by sol-gel, impregnation and microemulsion methods and characterized by X-Ray Diffraction (XRD), Fourier Transform Infra Red (FTIR), Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM), Energy Dispersive X-ray (EDX), Nitrogen Adsorption - Brunauer-Emmett-Teller (BET), and NH3-Temperature Programmed Desorption (TPD) methods. The Mo-SiO2 sample prepared by the sol-gel method exhibited the highest DHPM yield (87%), in free solvent with a reaction time of 30 min. The high efficiency, in the Biginelli reaction, of the Mo-SiO2 catalyst is due to its structural, textural and acid properties. Highly dispersed αMoO3 species of orthorhombic structure having a high contribution of strong acidic sites would be the active species in the Biginelli synthesis. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).